Motivating doctors into leadership and management: a cross-sectional survey. Issue 4 (9th July 2020) - Bäker, Agnes; Bech, Mickael; Geerts, Jaason; Maigaard Axelsen, Susanne; Ullum, Henrik; Krabbe, Marie P; Goodall, Amanda H
Abstract : Purpose: Calls for doctors to enter management are louder as the benefits of medical leadership become clearer. However, supply is not meeting demand. This study asks doctors (physicians): what might encourage you to go into leadership, and what are the disincentives? The same was asked about leadership training. First, the paper tries to understand doctors' motivation to lead, specifically, to explore the job characteristics that act as incentives and disincentives. Second, the study points to organisational obstacles that further shrink the medical leadership pipeline. Method: Doctors were surveyed through the Organization of Danish Medical Societies. Our key variables included: (1) the incentives and disincentives for doctors of going into leadership and management and (2) the motivation to participate in leadership training. Our sample of 3534 doctors (17% response) is representative of the population of doctors in Denmark. Findings: The main reason why doctors are motivated towards leadership is to make a difference. They are put off by fears of extra administration, longer hours, burnout, lack of resources and by organisational cultures resistant to change. However, doctors are aware of their need for leadership development prior to entering management. Practical implications: To improve succession planning, health systems should adapt to reflect the incentives of their potential medical leaders. Leadership training is also essential. These changes are especially important now; medical leaders are linked positively to organisational and patient outcomes and have been central in responding to COVID-19, stress and burnout among clinical staff continues to rise, and health systems face recruitment and retention challenges.